"Lazarus response" of nivolumab in a frail patient with non‐small‐cell lung cancer. Issue 5 (8th June 2017) - Takeda, Takayuki; Takeuchi, Mayumi; Nishimi, Yurika; Saitoh, Masahiko; Takeda, Sorou
Abstract : Lung cancer has aggressive behaviour which often progresses rapidly with disseminated disease and leads to poor performance status (PS) in patients. Because cytotoxic chemotherapy is not recommended under these conditions, there are currently no alternative therapeutic options other than providing supportive care. Immune checkpoint inhibitors have been developed, but their efficacy and tolerability have not been fully investigated in patients with poor PS. A 72‐year‐old male patient with lung adenocarcinoma harbouring no EGFR‐sensitizing mutation or ALK translocation was receiving second‐line chemotherapy with S‐1 monotherapy when he complained of worsening dyspnea. Chest computed tomography (CT) demonstrated disease progression at the primary site that was accompanied by bilateral pulmonary lymphangitic carcinomatosis, which was the cause for respiratory failure. Oxygen administration at 10 L/min was required due to the rapid progression of the tumour that resulted in poor PS. A retrospective study was conducted to assess the upregulation of programmed death ligand 1 (PD‐L1) using anti‐PD‐L1 22C3 mouse monoclonal primary antibody and found that the PD‐L1 expression was 50–60% (i.e. tumour proportion score ≥50%). Since cytotoxic chemotherapy could not be considered due to a poor PS of 4, nivolumab was cautiously administered. After the introduction of nivolumab, ground glass opacities, and consolidations on chest CT temporarily deteriorated on day 4 without any other clinical signs and symptoms. The reevaluation on day 10 demonstrated significant improvements on chest X‐ray. Then the patient was subsequently diagnosed with pseudoprogression. Thereafter, both the respiratory status and the PS improved gradually. The PS recovered to baseline conditions with oxygen administration at 1 L/min after four cycles of treatment. The patient currently remains at a PS of 1 and is progression‐free for eight months after the introduction of nivolumab. Abstract : Lung cancer has aggressive behaviour which often progresses rapidly with disseminated disease and leads to poor performance status (PS) in patients. Since cytotoxic chemotherapy is not recommended under these conditions, there are currently no alternative therapeutic options other than providing supportive care. Immune checkpoint inhibitors have been developed, but their efficacy and tolerability have not been fully investigated in patients with poor PS. We describe a case of "Lazarus response" of nivolumab in a frail patient with non‐small‐cell lung cancer.